2014
DOI: 10.1590/1414-431x20133554
|View full text |Cite
|
Sign up to set email alerts
|

Salt-induced epithelial-to-mesenchymal transition in Dahl salt-sensitive rats is dependent on elevated blood pressure

Abstract: Dietary salt intake has been linked to hypertension and cardiovascular disease. Accumulating evidence has indicated that salt-sensitive individuals on high salt intake are more likely to develop renal fibrosis. Epithelial-to-mesenchymal transition (EMT) participates in the development and progression of renal fibrosis in humans and animals. The objective of this study was to investigate the impact of a high-salt diet on EMT in Dahl salt-sensitive (SS) rats. Twenty-four male SS and consomic SS-13BN rats were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…Finally, the adherens junction pathway was enriched in the KSD-NTN group compared to the KSD-HTN group. In a previous study in rats, expression of the adherens junction protein E-cadherin was shown to be negatively correlated with BP [55]. These results indicate that the adherens junction pathways of the urinary microbiome may be involved in the occurrence or development of KSD-HTN.…”
Section: Discussionmentioning
confidence: 55%
“…Finally, the adherens junction pathway was enriched in the KSD-NTN group compared to the KSD-HTN group. In a previous study in rats, expression of the adherens junction protein E-cadherin was shown to be negatively correlated with BP [55]. These results indicate that the adherens junction pathways of the urinary microbiome may be involved in the occurrence or development of KSD-HTN.…”
Section: Discussionmentioning
confidence: 55%
“…Immunohistochemistry was conducted as previously reported [21]. Briefly, serial 5 µm paraffin-embedded tissue sections were dewaxed and rehydrated.…”
Section: Methodsmentioning
confidence: 99%
“…The primers employed in this study are shown in Table 1. The protocol for RT-PCR was based on our previous method [21]. The mRNA expression values are shown in folds of mRNA expression in the tissues of SD rats fed with normal salt diet.…”
Section: Methodsmentioning
confidence: 99%
“…Salt overload greatly contributes to the development and progression of hypertension [ 1 , 2 ]. Kidney and the vasculature are two critical parts of the body that regulate sodium balance, which ultimately develop into aberrant structures and dysfunction in high-salt diets [ 3 5 ]. Despite the detrimental effects of salt on the genesis of hypertension and sodium-regulated organs, humans and animals have various compensatory pathways to maintain sodium balance under high-salt conditions.…”
Section: Introductionmentioning
confidence: 99%